(untitled) (Journal of Educational Sciences, 2020)
This article examines the positive state of a person that arises under the influence of various situa- tions as well as the place of humor in the fight against negative situations and its relationship with intel- ligence. Humor has a special place in everyone’s life. The formation of coping strategies is its positive impact. Different types of humor are considered – irony, parody, satire, anecdote, pun, etc. There are two aspects of humor: cognitive and emotional. If the cognitive aspect is aimed at regulat- ing relations between people, the emotional aspect contributes to the emergence and preservation of a positive mood in the interpersonal space. Based on the works of foreign and domestic scientists, the features and significance of humor as an integral part of social and emotional intelligence have been analyzed. The study also included an empirical study involving 119 students aged 17 to 22. The methods of R. Martin and G. Lefkurt “The Coping Humor Scale” was used in the diagnosis (CHS The Coping Humor Scale). As a result of the study, the level of students’ sense of humor in emergency situations was deter- mined and analyzed. Key words: social intelligence, emotional intelligence, humorous abilities, stress, coping.